The Relationship between Knowledge and Stress Felt by Teachers of Economics Implementing Kurikulum Tingkat Satuan Pendidikan - Lisa Agustina; Nor Aishah Buang; Mohammad Hussin (Proceedings of AICS - Social Sciences, 2016)
The purpose of this study was to identify the relationship between knowledge and stress  amongst  teacher  of  economics in implementing  kurikulum  tingkat  satuan pendidikan. This study used a questionnaire with 109 teachers from twelve middle schools in Aceh Besar, Indonesia, with overall reliability of 0.930. Descriptive statistical tests found that the level of knowledge of the teachers was at a moderate level with an overall mean value of 3.04. Meanwhile the level of stress was at a high level with an overall mean value at 3.56. An inferential statistical correlation test was used to test an hypotheses. The inferential statistical test found that there was a negative relationship between the level of knowledge  and  the  level  of  stress.  It  can  be concluded that the implementation of the curriculum gave the most teachers stress.